Why Law? Examining the Factors that Influence the Decision to Undertake a Law Degree - Danielle Bozin; Gary Mortimer; Shasha Wang (Legal Education Review)
Existing research is largely silent on determining what factors influence individuals to undertake a law degree. Are they deeply intrinsic drivers like ‘self-efficacy’ or ‘self-confidence’, and how might extrinsic influences, such as family, teachers, or friends’ impact on those drivers? To address these questions, data were attained from 378 commencing students enrolled across three Australian law schools. Results indicate students with higher levels of self-efficacy and self-confidence are more likely to be satisfied with their decision to study law and pursue a law career. The influence of ‘teachers’ on a student’s ‘satisfaction with their choice’ was only significant for students who were also influenced by their ‘family’ – the more support from teachers and family members increased a student’s level of satisfaction. Friends only influenced a students’ intention to pursue a career in law, but not their satisfaction with their choice to pursue a law degree. This is the first study to determine the intrinsic motivations that impact a student’s choice to undertake a law degree and what extrinsic factors influence that choice.